2011
DOI: 10.1016/j.jappgeo.2011.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Noise characteristics of an electromagnetic sea-ice thickness sounder on a fixed wing aircraft

Abstract: In this paper, the noise sources of an airborne electromagnetic frequency domain instrument used to measure sea-ice thickness are studied. The antennas are mounted on the wings of an aircraft. The paper presents real data examples showing that strong noise limited the accuracy of the thickness measurement to ± 0.5 m in the best case. Even drift correction and frequency filtering did not reduce the noise to a level necessary for sea ice thickness measurements with an accuracy of 0.1 m. We show results of 3D fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Hendricks (2009) and Rabenstein et al, (2011) developed a 3D forwardmodeling code to simulate HEM data for 2D and 3D sea-ice structures, and to study the EM-fuselage coupling for a fixed-wing EM system operated by AWI. The model is based on the commercial software package Comsol Multiphysics® and solves the 3D EM problem on unstructured grids using a finite-elements method.…”
Section: D Em Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…Hendricks (2009) and Rabenstein et al, (2011) developed a 3D forwardmodeling code to simulate HEM data for 2D and 3D sea-ice structures, and to study the EM-fuselage coupling for a fixed-wing EM system operated by AWI. The model is based on the commercial software package Comsol Multiphysics® and solves the 3D EM problem on unstructured grids using a finite-elements method.…”
Section: D Em Modelingmentioning
confidence: 99%
“…Research institutes in Norway, China, and Canada have recently purchased systems equivalent to the smallscale bird developed by AWI (Pfaffling et al, 2004;Haas et al, 2006). AWI experimented with a fixed-wing adaptation with limited success (Rabenstein et al, 2011). The University of Alberta (Canada) is testing a dual-frequency (4 and 170 kHz) HEM system with integrated lidar scanner (C. Haas, personal communication, 2011).…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…By applying a suitable calibration, they removed the secondary field generated by the aircraft. Leväniemi et al (2009) and Rabenstein et al (2011) found that the wing flexure is the primary cause of strong electromagnetic noise. To the best of our knowledge, there have been no previous analyses of noise and interference effects with fixed-wing airborne far-field electromagnetic measurements in the VLF and LF bands.…”
mentioning
confidence: 99%